Reverse genetic approaches allowing the characterization of the rabies virus street strain belonging to the SEA4 subclade - Kawaguchi, Nijiho; Itakura, Yukari; Intaruck, Kittiya; Ariizumi, Takuma; Harada, Michiko; Inoue, Satoshi; Maeda, Ken; Ito, Naoto; Hall, William W.; Sawa, Hirofumi; Orba, Yasuko; Sasaki, Michihito (Scientific Reports, 2024)
Rabies virus (RABV) is the causative agent of rabies, a lethal neurological disease in mammals. RABV strains can be classified into fixed strains (laboratory strains) and street strains (field/clinical strains), which have different properties including cell tropism and neuroinvasiveness. RABV Toyohashi strain is a street strain isolated in Japan from an imported case which had been bitten by rabid dog in the Philippines. In order to facilitate molecular studies of RABV, we established a reverse genetics (RG) system for the study of the Toyohashi strain. The recombinant virus was obtained from a cDNA clone of Toyohashi strain and exhibited similar growth efficiency as the original virus in cultured cell lines. Both the original and recombinant strains showed similar pathogenicity with high neuroinvasiveness in mice, and the infected mice developed a long and inconsistent incubation period, which is characteristic of street strains. We also generated a recombinant Toyohashi strain expressing viral phosphoprotein (P protein) fused with the fluorescent protein mCherry, and tracked the intracellular dynamics of the viral P protein using live-cell imaging. The presented reverse genetics system for Toyohashi strain will be a useful tool to explore the fundamental molecular mechanisms of the replication of RABV street strains.